Developing ISpring Suite 8 Based Qmath Learning Media on Polyhedron Lesson for Junior High School Students - Tayeb, Thamrin; Ilhamsyah; Mattoliang, Lisnasari Andi ,; Majid, Ahmad Farham; Kusumayanti, Andi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to develop the ISpring Suite 8 based Qmath learning media on polyhedron lesson for junior high school students that is valid, practical, and effective. This type of research was Research & Development. The development model used in this study was ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The population of this study was eight grade students in Al-Huda IT Junior High School with the study sample was students of VIII A class in Al-Huda IT Junior High School. The research trials were carried out twice, namely small-scale and large-scale trials. The research instruments used were expert validation sheet, student questionnaire response, and learning achievement test. The results showed that the average score of the validation result of ISpring Suite 8 based Qmath learning media was 3 in the valid category, the average score obtained from the student questionnaire response was 3.41, indicated that this learning media was practical to use, and the average score of learning outcome of students who became the study sample was 78,02 and it fulfilled the effective criteria. It can be concluded that, ISpring Suite 8 based Qmath learning media on polyhedron lesson fulfilled the criteria of validity, practicality, and effectiveness.